BIODIVERSITY MODULE BASED ON PROBLEM-BASED LEARNING LOCAL WISDOM ASSISTED BY AUGMENTED REALITY: IMPROVING STUDENTS' CRITICAL THINKING - Iwan, Iwan; Jeni, Jeni; Nurfathurrahmah, Nurfathurrahmah (JURNAL EDUSCIENCE, 2025)
Purpose – The purpose of this study was to develop a student teaching module for biodiversity material oriented to Problem Based Learning integrated with local wisdom and assisted by augmented reality media to improve students' critical thinking skills.Methodology- The research method refers to the type of ADDIE research and development. The sample in this study was students of YAPIS High School who were taken using the total sampling technique. The data collection instruments were validation sheets and questionnaires to determine the validity and student responses to student books and the provision of critical thinking skills test questions. The data analysis technique was carried out descriptively by calculating the validation results, analyzing student response questionnaires and students' critical thinking skills.Findings – The findings are the media and material expert validation test obtained 92.50% (very valid), the validation of critical thinking skills questions obtained 91.11% (very valid). Practicality obtained a value of 83.86% (very practical). The average value of students' critical thinking skills was 65.00 indicating that the value of students' critical thinking skills was in the good category.Contribution – The integration of local wisdom into PBL-oriented modules supported by augmented reality technology has great potential in improving students' critical thinking skills. Through local wisdom, students are invited to learn from cultural values related to nature conservation, while PBL allows them to actively seek solutions to relevant environmental and biodiversity problems. The biodiversity teaching module oriented to problem-based learning integrated with local wisdom and assisted by Augmented Reality that was developed can improve students' critical thinking skills